The Arab-Israeli conflict - Schulze, Kirsten E. (London ; New York : Routledge, Taylor & Francis Group, 2017)
"Analyzes the Arab-Israeli conflict, exploring the particular dynamics of this conflict and the numerous attempts at its resolution"--Provided by the publisher.
Part 3. The Middle East Peace Process. From Madrid To The Second Intifada -- Israel, Jordan, Syria And Lebanon, 1994--2015 -- Wars 2006-2014.
Includes bibliographical references (pages 173-188) and index.
1 2
Keywords: Arab-Israeli conflict; Arab-Israeli conflict -- 1993- -- Peace; Arab-Israeli conflict; Arab-Israeli conflict -- Peace; Since 1993